2008
DOI: 10.1007/s11095-008-9719-8
|View full text |Cite
|
Sign up to set email alerts
|

A Fibrin Glue Composition as Carrier for Nucleic Acid Vectors

Abstract: COPROGs co-lyophilized with fibrinogen are a simple basis for an injectable fibrin gluebased gene-activated matrix. The preparation can be used is complete analogy to fibrin glue preparations that are used in the clinics. However, further improvements in transgene expression levels and persistence are required to yield cartilage regeneration in the osteochondral defect model chosen in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…For cartilage tissue engineering purposes, FG scaffolds with nonviral copolymer-protected polyethylenimine-DNA vectors achieved sustained release of the gene over 20-day period and successful in vitro transfection of human keratinocytes and rabbit articular chondrocytes. 28 Nonetheless, FG formulation for AAV2 delivery has not been optimized. The fibrinogen/thrombin concentration in the FG preparation has been shown to affect the structural properties of the scaffold, and in turn influence the proliferation rate and morphology of hMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cartilage tissue engineering purposes, FG scaffolds with nonviral copolymer-protected polyethylenimine-DNA vectors achieved sustained release of the gene over 20-day period and successful in vitro transfection of human keratinocytes and rabbit articular chondrocytes. 28 Nonetheless, FG formulation for AAV2 delivery has not been optimized. The fibrinogen/thrombin concentration in the FG preparation has been shown to affect the structural properties of the scaffold, and in turn influence the proliferation rate and morphology of hMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that diluted FG produces a more open fibrin network compared with undiluted FG scaffolds, 27 and that FG can act as an efficient scaffold for gene delivery. [28][29][30] In the current study, we investigated the effect of different fibrinogen dilutions during the preparation of FG scaffold on the delivery of AAV2 and their early effects on human BM-MSC (hBM-MSC) chondrogenesis in vitro. The aim of this study was to test the hypotheses that diluted FG scaffolds will release more viral particles, result in higher transduction efficiency, and increase the chondrogenic potential of transduced hBM-MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can be assumed that COPROGs are suited to be embedded both in the gel phase and the MBCP ™ solid phase of the GAMBA composite matrix (Figure 1 ). As described previously (31) COPROGs are assembled in aqueous suspension. Hence, we have determined in a fi rst step the maximum volume of water per weight of MBCP ™ that the granules can soak.…”
Section: Coprogs On Mbcp ™ ™mentioning
confidence: 99%
“…In general, efficacy and specificity of delivery tools to target tumour sites are improving. These approaches include copolymer-protected vectors (Schillinger et al 2008), liposomal tools with tumour-targeting affinities (Templeton 2009) and viral vectors with enhanced anti-tumour properties (Alemany 2009). Thus, these findings point towards potential approaches to restore endogenous BMP levels in adrenocortical carcinoma cells for the modulation of their functional properties and malignant potential providing hope for a specific and potent therapy of ACC patients with reduced side effects in the future.…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 99%